Surgery for parathyroid microadenomas: patient characteristics, localization success and operative cures. Issue 1 (14th June 2016) - Suter, Katherine J. L.; Johnson, William; Yeung, Meei; Serpell, Jonathan; Lee, James C.; Grodski, Simon
Abstract : Background: In recent years, patients with primary hyperparathyroidism (PHPT) are being diagnosed earlier, with milder elevations in parathyroid hormone (PTH) and serum calcium. We aimed to investigate whether adenoma size reflects biochemical severity of presentation and influences localization of pre‐operative scans. Methods: A total of 630 consecutive patients undergoing parathyroidectomy for PHPT were recruited into either the microadenoma (≤200 mg) or macroadenoma (>200 mg) group. Pre‐operative serum calcium, PTH, rates of minimally invasive parathyroidectomy and bilateral neck exploration, localization of adenomas with pre‐operative ultrasound and sestamibi (MIBI) scans, cure rates and other demographic parameters were compared. The data were analysed using Student's t ‐test, Chi‐squared test, linear and multiple regression analyses. Results: Patients in the microadenoma group had significantly lower pre‐operative serum calcium ( P < 0.001) and PTH ( P < 0.001), less accurate MIBI ( P < 0.001) and ultrasound ( P < 0.001), lower cure rates ( P = 0.04) and were more likely to undergo bilateral neck exploration ( P = 0.001). However, multivariate analysis revealed that microadenomas are most strongly associated with the findings of less accurate MIBI ( P = 0.03) and lower pre‐operative calcium ( P = 0.04). Conclusion: In conclusion, smaller adenomas are strongly associated with biochemically milder PHPT and less accurate localization studies. Therefore, microadenomas continue to present as a challenge in both diagnosis and management.